Redefining Clean Water Regulations Reduces Protections for Wetlands and Jurisdictional Uncertainty - Walsh, Riley; Ward, Adam S. (Frontiers in Water, 2019)
The 2015 Clean Water Rule is being enforced in 26 states, with a legal stay resulting in the prior rules being enforced in the remaining 24 states, and a proposed re-definition open for public comment. These rules define which streams and wetlands are protected by the Clean Water Act and which require a permit for development, fill, or discharge of water and pollutants. In the Wabash River Basin, as much as 39% of wetlands in the basin would lose their current federal protections. The 2015 Clean Water Rule did not expand jurisdictional scope, but the proposed rule would significantly contract protections in our study basin. The proposed re-definition shifts uncertainty from the “significant nexus” test to definitions of stream intermittency and typical hydrologic conditions.